Evaluation of weed management approaches on weed dynamics, yield and economics of puddled rice under different plant techniques - M, Vikram Sai; G, Murugan; Kumar, Sai (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted in January to May, 2022 (Navarai) to find out the effective weed management practices in puddled rice. The experiment was carried out in a split-plot design, which included two planting techniques viz., drum seeded rice and system of rice intensification (SRI) in main plot, as well as eight weed management practices viz., hand weeding, cono weeding, pretilachlor, bispyribac sodium and fenoxaprop - p - ethyl as pre and post emergence application in sub plot. The results of the experiment demonstrated that among the planting techniques and weed management practices tested, the system of rice intensification and sequential application of pretilachlor @ 0.5 kg a.i ha-1 fb bispyribac sodium @ 20 g a.i ha-1 has revealed lowest weed density (39.67, 71.25 and 17.02, 33.97 no m-2) and highest weed control efficiency (55.89, 65.78 and 84.99, 82.33 %) grain yield (4.55 and 5.47 t ha-1), gross and net income (Rs. 12116 and Rs. 64336 ha-1). However, drum seeded rice resulted higher return-1 rupee invested due to lower cost of cultivation. Hence, the SRI planting method with sequential application of pretilachlor @ 0.5 kg a.i ha-1 followed by bispyribac sodium @ 20 g a.i ha-1 has proven to be effective in controlling weeds and achieving higher grain yield and net income.